The Ephemeral Term “Sustainable Development” in Current EU Policies - Zavřelová Veronika; Pelikánová Radka MacGregor (Folia Oeconomica Stetinensia)
The term “sustainable development” is an omnipresent expression reaching the dimension of a command in the EU under the leadership of Ursula von der Leyen. However, this is an ephemeral term with ambiguous and contradictory meanings which is employed in a particular manner by current EU policies.